2018
DOI: 10.1016/s0140-6736(18)32486-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy to the primary tumour for newly diagnosed, metastatic prostate cancer (STAMPEDE): a randomised controlled phase 3 trial

Abstract: SummaryBackgroundBased on previous findings, we hypothesised that radiotherapy to the prostate would improve overall survival in men with metastatic prostate cancer, and that the benefit would be greatest in patients with a low metastatic burden. We aimed to compare standard of care for metastatic prostate cancer, with and without radiotherapy.MethodsWe did a randomised controlled phase 3 trial at 117 hospitals in Switzerland and the UK. Eligible patients had newly diagnosed metastatic prostate cancer. We rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
807
4
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,009 publications
(853 citation statements)
references
References 30 publications
19
807
4
23
Order By: Relevance
“…Although our PDRT could not completely prevent urinary obstruction, several retrospective studies proposed that definitive prostate‐directed therapy reduces the risk of urinary obstruction when compared to ADT alone . Recently, Parker et al evaluated whether radiotherapy for the prostate would improve symptomatic local events in newly diagnosed mPCa patients. This trial (STAMPEDE trial) did not support the benefits for local prostate therapy to prevent newly diagnosed mPCa patients from developing symptomatic local events such as the need for new urinary catheterization, ureteric stents and transurethral resection of prostate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although our PDRT could not completely prevent urinary obstruction, several retrospective studies proposed that definitive prostate‐directed therapy reduces the risk of urinary obstruction when compared to ADT alone . Recently, Parker et al evaluated whether radiotherapy for the prostate would improve symptomatic local events in newly diagnosed mPCa patients. This trial (STAMPEDE trial) did not support the benefits for local prostate therapy to prevent newly diagnosed mPCa patients from developing symptomatic local events such as the need for new urinary catheterization, ureteric stents and transurethral resection of prostate.…”
Section: Discussionmentioning
confidence: 94%
“…Systemic Therapy in Advancing or Metastatic Prostate Cancer: Evaluation of Drug Efficacy (STAMPEDE) trial compared standard of care and radiotherapy for the prostate versus standard of care for overall survival in newly diagnosed mPCa patients . This randomized phase 3 trial showed that radiotherapy for the prostate did not improve overall survival for unselected patients (HR 0.92; 95%CI: 0.80‐1.06), whereas prostate radiotherapy did improve overall survival in patients with a low metastatic burden (HR 0.68; 95%CI: 0.52‐0.90).…”
Section: Introductionmentioning
confidence: 99%
“…The use of EBRT in prostate cancer patients with metastases has historically been limited to treatment with palliative intent. Several studies have proposed that radiotherapy to the prostate would improve the overall survival of patients with metastatic prostate cancer . These data are expected to change the standard of practice, as it is anticipated that patients will be offered the combination of systemic therapy and local radiotherapy, in particular, for patients with low‐volume oligometastatic prostate cancer.…”
Section: Radiotherapy For Metastatic Prostate Cancermentioning
confidence: 99%
“…In patients with disseminated mHSPC, the majority of available data have been derived from retrospective analyses, but the results from 2 prospective studies recently were presented …”
Section: Introductionmentioning
confidence: 99%